Adenoid cystic carcinoma cytology: Salivary gland and nonsalivary gland. Issue 12 (18th August 2020) - Chowsilpa, Sayanan; An, Daniel; Maleki, Zahra
Abstract: Objectives: Adenoid cystic carcinoma (ACCA) is an uncommon primary malignancy of salivary glands and rarely nonsalivary tissue. This study aims to evaluate the diagnostic accuracy of ACCA on fine needle aspiration (FNA) material and the associated challenges. Methods: A search on electronic pathology database from 2006 to 2016 at The Johns Hopkins Hospital found 83 cytology specimens diagnosed as ACCA, 49 with histology follow‐up. Results: Fifty‐two females and 31 males were found ranging from 37 to 95 years old (mean 62.5). The tumor size was 1 to 11.5 cm (mean 3.4). FNAs were performed on 46 salivary glands (54.88%), 12 head and neck masses (14.45%), 9 lymph nodes (10.84%), 9 tracheas/lungs (10.84%), 4 vaginal/perineum/gluteal masses (4.82%), and one for each kidney, liver and abdominal/pelvic mass (1.21%). 83 FNA diagnoses revealed 3 nondiagnostics (3.61%), 20 neoplasms with unspecified features (24.10%), 30 basaloid neoplasms (36.14%), 18 ACCA (21.69%), and 12 other malignancies (14.46%). The accuracy of FNA in diagnosis of ACCA comparing to histologic follow‐up in 49 cases was 87.5% sensitivity, 66.67% specificity, with 92.11% positive predictive value and 54.55% negative predictive value. The most common mimicker was pleomorphic adenoma. Conclusion: ACCA can be diagnosed not only in the salivary gland FNAs, but also respiratory tract, intra‐abdominal, kidney, and gynecologic regions. FNA is a preferred technique to assess mass lesions. However, a diagnosis of ACCA on FNA material should be rendered with caution since there are benign and malignant neoplasms with overlapping features. Awareness of prior medical history and ancillary studies can improve the diagnosis.